SER. Juego que enseña a los niños a ser empáticos y valorar las diferencias propias y las de los demás (2021)
In our society there is discrimination and intolerance towards those who express themselves in a way different from the gender paradigm, this as a result of the establishment of a culture that determines what men and women should do since we are children. From that moment, everything we interact with is divided by gender, clothing, room decoration and of course, toys. The latter play a fundamental role in the establishment of these stereotypes, since the game plays the role of preparing us for adult life and especially in the preoperational stage (among children from 3 to 6 years old), which is when symbolic play appears as a representation of everyday life, but the child is able to separate the meaning of the objects and give them their own meaning, which is why, at this stage, it is essential that the child is not reinforced with gender stereotypes, but rather is encourage exploration of your own personality. In this sense, design is a mediator in education about gender paradigms and has the responsibility to limit or multiply the child's options so that they accept the differences of others and can express themselves freely. This project is focused on allowing children to express themselves freely through the construction of their own characters and their own world, using the design of game objects for children between 3 and 5 years of age as an educational tool that promotes principles such as empathy and the value of diversity. In the project, research methods such as the survey and the interview were used, the first was used to find out what the generation of millennials thought about the importance of educating about gender expression and the second, as a way of knowing The opinion of non-traditional gender people towards what they thought was necessary in Colombian society so that there would be more tolerance towards gender expression. In addition, consultancies were carried out with psychologists and industrial designers specialized in the design of experiences and with knowledge in children's products, which helped in the specific approach of the project. Verifications were also carried out with the users that allowed making formal and functional decisions of the object in order to fully comply with the objective. As a result, on the one hand, it was clear the division and gender stereotypes that exist in traditional toys and how the new generations support the deconstructing of these stereotypes through teaching their children. On the other hand, it was also evident how the game plays an essential role in the development of gender stereotypes and how education is relevant in the process of construction of these concepts and how by allowing them to create their own games, they we give the creative freedom to build your own personality and understand that others can be different. For this reason, the project allows the child to explore possibilities through configurations with the guidance of a tutor who transmits reflections through mini-games with the premise ¨valuing my differences and those of others, we will create a better world¨. (Barriga, 2021)